2021
DOI: 10.1111/adb.13114
|View full text |Cite
|
Sign up to set email alerts
|

Dual methylation and hydroxymethylation study of alcohol use disorder

Abstract: Using an integrative, multi-tissue design, we sought to characterize methylation and hydroxymethylation changes in blood and brain associated with alcohol use disorder (AUD). First, we used epigenomic deconvolution to perform cell-type-specific methylome-wide association studies within subpopulations of granulocytes/T-cells/ B-cells/monocytes in 1132 blood samples. Blood findings were then examined for overlap with AUD-related associations with methylation and hydroxymethylation in 50 human post-mortem brain s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 54 publications
3
26
3
Order By: Relevance
“…Of the three studies that assayed methylation in brain tissues 7,9,10 , we identified one CpG with look-up significance and three annotated genes that overlapped with our results. cg00402668 (intergenic) reached look-up significance in the DLPFC EWAS and was among the top 20 sites with AUD-associated hydroxymethylation in BA10 from Clark et al 10 .…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…Of the three studies that assayed methylation in brain tissues 7,9,10 , we identified one CpG with look-up significance and three annotated genes that overlapped with our results. cg00402668 (intergenic) reached look-up significance in the DLPFC EWAS and was among the top 20 sites with AUD-associated hydroxymethylation in BA10 from Clark et al 10 .…”
Section: Resultssupporting
confidence: 65%
“…. We did not observe significant enrichment between our results and those from Clark et al (Table S9) 10 .…”
contrasting
confidence: 67%
See 2 more Smart Citations
“…While exploratory methylome-wide analyses in the human brain found no global differences between alcohol dependent and control subjects ( Manzardo et al, 2012 ; Clark et al, 2022 ), the focused approaches were more successful. The authors tested the hypothesis that methylation of prodynorphin (Pdyn) CpG-SNPs in the PFC is associated with alcohol misuse ( Taqi et al, 2011 ).…”
Section: Cpg Methylation and Alcohol Usementioning
confidence: 99%